CSR Engagements and its Communication Strategies - Review of Literature - Srivastava, Anjani Kumar; Jonjua, Mehak (Journal of Advanced Research in Journalism & Mass Communication, 2018)
CSR (Corporate social responsibility) activities done by corporate companies are now integral management strategies to enhance their brand value and image. How companies should communicate about the corporate social responsibility engagements to the stakeholders, is the subject of debate and research, today. CSR communication is now important part of ensuring future businesses. The corporations operating in European countries and USA have been doing lot of corporate social responsibility activities and also communicating (reporting to its stakeholders) by the use of different media platforms including digital and social media, whereas corporate companies in India have started recently to communicate and give publicity to their CSR activities via print and electronic media as well as social and digital media, only since the last 2 years. As the Parliament of India has made it mandatory to do lot of CSR activities in the last year and now companies those have turnover of Rs.500 crore and above are bound to spend 2% of their annual turnover on CSR activities. It is important to investigate whether companies in India are enough aware of adopting different CSR communication strategies that could help enhance their brand image and brand value after doing various CSR activities. This study has focused upon secondary data available in various research papers and CSR reports where companies adopted different communication strategies. This analytical study has attempted to review of literature available on investigating on companies about whether various communication strategies were adopted or not and if these were used how it helped increasing the companies’ image among consumers and stakeholders as well as consumer loyalty for the product and services which company provided. How to cite this article: Srivastava AK, Jonjua M. CSR Engagements and its Communication Strategies - Review of Literature. J Adv Res Jour Mass Comm 2018; 5(1&2): 11-17. DOI: https://doi.org/10.24321/2395.3810.201803